AKADEMI FUTSAL DI BANJARBARU - Muhammad Azisi Saad; Prima Widia Wastuty (UNIVERSITAS LAMBUNG MANGKURAT, 2025)
The design of a Futsal Academy in Banjarbaru aims to create a functional and comfortable space to support the training process of futsal athletes in Banjarbaru, South Kalimantan, to produce professional futsal players who can compete at both local, national, and even international levels. The contemporary architectural approach is used as the method in designing this Futsal Academy. The main focus of the design starts from the processing of outdoor and indoor spaces, which are the main objects, by maximizing functional principles. The use of the Contemporary Functional concept aims to create a productive space to support all activities of the users of the Futsal Academy area, thus realizing the maximum training and learning process at the Futsal Academy in Banjarbaru.